2013
DOI: 10.2134/agronj2012.0221
|View full text |Cite
|
Sign up to set email alerts
|

Row Spacing and Nitrogen Fertilizer Effect on No‐Till Oat Production

Abstract: A major challenge in agriculture is to enhance crop production in an environmentally sustainable fashion to meet the needs of a growing population given the continual decline in the global arable land base. The objectives of the study were to study the interaction between row spacing and N rate in oat (Avena sativa L.) on plant establishment and development, biomass production, grain quality, and grain yield under a no‐till production system. Four row spacing (25, 30, 35, and 40 cm) and five rates of N fertili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 43 publications
7
22
0
Order By: Relevance
“…Jacobs and Pearson (1992) confirmed the importance of physical ear size restrictions (greater spikelet number as the ear surface increased regardless of the N supply). From a compendium of other findings (Tollenaar and Daynard, 1978;Wilson and Allison, 1978;Salvador, 1984;Pearson, 1991, 1992;Lemcoff and Loomis, 1994;Otegui and Melón, 1997;Otegui and Bonhomme, 1998;Roth et al, 2013) the data suggest that maximum PKn did not change with time in nonprolific maize hybrids (even in nontransgenic "drought-tolerant" materials). The RKF was significantly affected by hybrid (hybrid 1 slightly less than hybrid 2), PD, and N rate single treatment factors (data not shown).…”
Section: Potential Kernel Number and Reproductive Relative Kernel Faimentioning
confidence: 77%
See 1 more Smart Citation
“…Jacobs and Pearson (1992) confirmed the importance of physical ear size restrictions (greater spikelet number as the ear surface increased regardless of the N supply). From a compendium of other findings (Tollenaar and Daynard, 1978;Wilson and Allison, 1978;Salvador, 1984;Pearson, 1991, 1992;Lemcoff and Loomis, 1994;Otegui and Melón, 1997;Otegui and Bonhomme, 1998;Roth et al, 2013) the data suggest that maximum PKn did not change with time in nonprolific maize hybrids (even in nontransgenic "drought-tolerant" materials). The RKF was significantly affected by hybrid (hybrid 1 slightly less than hybrid 2), PD, and N rate single treatment factors (data not shown).…”
Section: Potential Kernel Number and Reproductive Relative Kernel Faimentioning
confidence: 77%
“…However, the hybrid effects on mean PKn were not significant (Table 4). From a compendium of other findings (Tollenaar and Daynard, 1978;Wilson and Allison, 1978;Salvador, 1984;Pearson, 1991, 1992;Lemcoff and Loomis, 1994;Otegui and Melón, 1997;Otegui and Bonhomme, 1998;Roth et al, 2013) the data suggest that maximum PKn did not change with time in nonprolific maize hybrids (even in nontransgenic "drought-tolerant" materials). Although further data should be assembled to be more conclusive, the effect of modern hybrids in establishing greater Kn seems to be directly associated with greater stress tolerance and lower SGR thresholds to set kernels (Echarte et al, 2004) and not by dramatic changes over time in PKn.…”
Section: Potential Kernel Number and Reproductive Relative Kernel Faimentioning
confidence: 77%
“…Using information from a meta-analysis performed by Akiyama et al (2010), the effect of nitrapyrin was calculated as achieving an average 39% reduction in N 2 O emissions. Another recent Indiana study (Omonode and Vyn 2013) observed an average 35% reduction in N 2 O emissions when nitrapyrin was used with sidedress N application at a single rate of 200 kg N ha −1 . A Colorado study (Halvorson et al 2010) found a 35% reduction in N 2 O emissions when Figure 1.…”
Section: Discussionmentioning
confidence: 97%
“…Currently, growers targeting high yields and high returns have started to apply in excess of 90 kg ha −1 of nitrogen (N) fertilizer to their oat crop; however, studies have not consistently supported this level of N fertilizer use. Previous studies observed optimal N responsiveness in oat in a range from 30 to 120 kg N ha −1 fertilizer (Brinkman & Rho, 1984; Lafond, May, & Holzapfel, 2013; May, Mohr, Lafond, Johnston, & Craig Stevenson, 2004; Pecio & Bichonìski, 2010). A study investigating the response of oat to N observed severe lodging after the N rate surpassed 84 kg N ha −1 followed by grain yield decreasing beyond this rate (Brinkman & Rho, 1984).…”
Section: Introductionmentioning
confidence: 95%